Mobilizing public sociology : scholars, activists, and Latin@ migrants converse on common ground - Carty, Victoria; Luévano, Rafael (Studies in critical social sciences, 2017)
Mobilizing Public Sociology , coedited by Victoria Carty and Rafael Luévano, combines theory and scholarly perspectives with a grassroots approach to challenges that Latin@ immigrants face in the United States. Public sociology calls for scholars and community activists and practitioners to engage in dialogue and to work together in the struggle for social justice. The contributors to this collection-scholars, immigrants, practitioners, and community activists-share their scholarly perspectives and personal experiences on a wide range of issues related to immigration, including deportation and criminalization, undocumented youth and higher education, legislation, and community activism. The collection encourages ongoing collaboration in dealing with some of the most pressing problems affecting our communities with the hope of breaking down barriers and misconceptions. Contributors are: Amelia Alvarez, Fawn Bekam, Victoria Carty, Kristin E. Heyer, Patricia Huerta, Rusty Kennedy, Oliver Lopez, Rafael Luévano, Raquel R. Marquez, Eileen McNerney, Patrick Murphy, Jerry Price, Lisa D. Ramirez, Harriett D. Romo, Suzanne SooHoo, Madeleine Spencer, Daniele Struppa, and Bishop Kevin William Vann.